Impact of a direct-fed microbial supplementation on intestinal permeability and immune response in broiler chickens during a coccidia challenge - Osho, Saheed; Bolek, Kevin; Saddoris-Clemons, Kari; Humphrey, Brooke; Garcia, Miriam (Frontiers in Microbiology, 2023)
Maintaining intestinal health supports optimal gut function and influences overall performance of broilers. Microlife ® Prime (MLP) contains a unique combination of four strains of Bacillus spp. selected to support a healthy gut which may improve performance. The aim of this study was to determine the effects of MLP supplementation on intestinal health and immunity of broilers challenged with a mixed coccidia infection during peak (0 to 6-day post infection (dpi)) and recovery phases (6 to 13 dpi). A total of 120 male, 4d-old Ross 708, broiler chicks were allotted to 3 treatment groups (8 replicate cages; 5 birds/cage) in a randomized complete block design. Treatments included a nonchallenge (NEG), a coccidia challenge (POS), and coccidia challenge fed MLP (5×10 5 CFU/g of diet). Diets were corn-soybean meal-based. At 11 days of age, all birds, except for NEG, were orally gavaged with 15 doses (3× the recommended commercial dose). On 6, 9, and 13 dpi, birds were gavaged with fluorescein isothiocyanate conjugate dextran (FITC-d). Plasma and mid-jejunum tissues were collected 2h later. On 6 dpi, duodenal lesions from 2 birds/cage were scored and droppings were collected for oocyst enumeration. Body weight gain (BWG) and feed conversion ratio (FCR) were calculated over the experimental period. Data were analyzed with GLIMMIX procedure of SAS. During the peak phase, POS birds had reduced BWG (23%) and FCR (15%) compared to NEG birds (P < 0.05), while birds fed MLP had similar BWG (209 and 208 g) and FCR (1.17 and 1.21) compared to NEG (P > 0.05). On 6 dpi, POS birds had higher lesion scores and oocyst shedding, 2× increase in serum FITC-d, and higher jejunum IL-10, and IFN-ϒ mRNA compared to NEG (P < 0.05). Birds fed MLP had reduced plasma FITC-d compared to POS birds (P < 0.05) and similar IL-10 and IFN-ϒ mRNA. On 13 dpi, birds fed MLP had lower plasma FITC-d, jejunum IL-10 and IFN-ϒ mRNA compared to POS birds (P < 0.05), but similar IL-10 to NEG birds (P > 0.05). This study confirms MLP improves intestinal health and positively modulates mucosal immune response post-coccidia challenge.